Physical activity and body mass in college students during the "new normal" associated with COVID-19 (Research, Society and Development, 2022)
Physical activity (PA) and body mass (BMI) were analysed in students of Medical Sciences of the University of Guayaquil in the year 2021. The population was 4504 students enrolled in 2021-II. Sampling was random probability and cluster sampling (363 subjects). A questionnaire and a registration form were used. Central tendency and variability statistics were calculated. Correlations (Spearman's Rho) were calculated between the dimensions of the variables. The results reveal that most of the students have little or no PA, however, this has not yet had an impact on their BMI values. Physical activity practice exhibits variability indicating the presence of a sedentary lifestyle, but also some frequent and intense PA. The BMI of the groups of students is in line with the norm weight, with cases of underweight and overweight students. The relationship between BMI and Physical Activity Level did not show significant relationships (p-value > 0.05). Despite the incidence of the patterns of confinement enforced by COVID-19, the indicators show that this has not had too great an impact on the characteristics analysed in the university students. Thus, the "new normality" has simply increased the pandemic of the lack of physical activity, which had already been pointed out in 2012. There is an urgent need to investigate new variables to better understand the phenomenon under study and to undertake multivariate studies that would make it possible to establish the clusters or health profiles of the students.